Comparison of brush and biopsy sampling methods of the ileal pouch for assessment of mucosa-associated microbiota of human subjects - Huse, Susan M; Young, Vincent B; Morrison, Hilary G; Antonopoulos, Dionysios A; Kwon, John; Dalal, Sushila; Arrieta, Rose; Hubert, Nathaniel A; Shen, Lici; Vineis, Joseph H; Koval, Jason C; Sogin, Mitchell L; et al. (Microbiome, 2014)
Mucosal biopsy is the most common sampling technique used to assess microbial communities associated with the intestinal mucosa. Biopsies disrupt the epithelium and can be associated with complications such as bleeding. Biopsies sample a limited area of the mucosa, which can lead to potential sampling bias. In contrast to the mucosal biopsy, the mucosal brush technique is less invasive and provides greater mucosal coverage, and if it can provide equivalent microbial community data, it would be preferable to mucosal biopsies. We compared microbial samples collected from the intestinal mucosa using either a cytology brush or mucosal biopsy forceps. We collected paired samples from patients with ulcerative colitis (UC) who had previously undergone colectomy and ileal pouch anal anastomosis (IPAA), and profiled the microbial communities of the samples by sequencing V4-V6 or V4-V5 16S rRNA-encoding gene amplicons. Comparisons of 177 taxa in 16 brush-biopsy sample pairs had a mean R2 of 0.94. We found no taxa that varied significantly between the brush and biopsy samples after adjusting for multiple comparisons (false discovery rate ≤0.05). We also tested the reproducibility of DNA amplification and sequencing in 25 replicate pairs and found negligible variation (mean R2 = 0.99). A qPCR analysis of the two methods showed that the relative yields of bacterial DNA to human DNA were several-fold higher in the brush samples than in the biopsies. Mucosal brushing is preferred to mucosal biopsy for sampling the epithelial-associated microbiota. Although both techniques provide similar assessments of the microbial community composition, the brush sampling method has relatively more bacterial to host DNA, covers a larger surface area, and is less traumatic to the epithelium than the mucosal biopsy.